Reconstructing Islamic Epistemology: A Philosophical Analysis of Amin Abdullah’s Integrative–Interconnected Paradigm - Rahmani, Diah Ayu; Najmi, Via Novelia; Dewi, Eva (Jurnal Pendidikan Agama Islam Al-Thariqah, 2026)
The separation between religious knowledge and modern sciences remains a major issue in contemporary Islamic thought, as it leads to fragmented and less integrated knowledge development. This condition not only divides sources of knowledge but also weakens the relationship between ethical, rational, and empirical dimensions in the construction of knowledge. In this context, the integration of knowledge becomes essential, particularly in Islamic education. This study aims to examine Amin Abdullah’s integrative-interconnected paradigm as an effort to reconstruct a more holistic Islamic epistemology. This research employs a qualitative approach using textual analysis of Abdullah’s works and relevant literature. The findings reveal that the integrative-interconnected paradigm connects three main domains religious texts (hadarat al-nash), scientific knowledge (hadarat al-'ilm), and philosophical reasoning (hadarat al-falsafah) within a dialogical framework. This approach rejects rigid separation between fields of knowledge as well as uncritical acceptance of modern science, emphasizing the interaction between textual, empirical, and rational dimensions in developing comprehensive knowledge. The novelty of this study lies in positioning the integration of knowledge as a critical and reflective effort rather than merely a pedagogical agenda. However, this research is limited to conceptual analysis, suggesting the need for further studies on its practical implementation in Islamic education, particularly in curriculum development and learning practices